Divided by the Market, Divided by the State: Distribution, Redistribution and Welfare Attitudes in 47 Countries. (21st September 2016) - Wulfgramm, Melike; Starke, Peter
Abstract : This article examines the impact of income inequality and welfare state context on the extent to which the rich and poor share similar attitudes towards redistribution. It asks whether and how differences in attitudes, particularly those between income groups, are shaped by inequality and redistributive efforts. Based on a multi‐level analysis of individual survey data across 47 countries at three points in time, the article shows that such an interaction of individual characteristics and the macro‐context indeed matters considerably. While material self‐interest, unsurprisingly, explains part of the individual differences, the analysis also shows, for the first time, that both high inequality and strongly redistributive policies divide public opinion along the lines of socioeconomic position. Put differently, while market inequality may be associated with less cohesive attitudes, a highly redistributive welfare state does not seem to foster agreement among the public, either. These findings have important policy implications for advanced welfare states, including a renewed emphasis on 'predistribution' (i.e., policies that influence the primary distribution of income) in order to avoid the scenario of intensified redistributive conflicts.